Future aerial sustainable and environment-friendly transport using stratospheric platforms - Ayodele A. Periola; Opeyeolu Timothy Laseinde; Olugbenga K. Ogidan (Frontiers in Computer Science)
Technological advances play an important role in future transport. Currently, assets such as fossil-fuel-based terrestrial vehicles, hybrid terrestrial vehicles and non–fossil fuel-based terrestrial vehicles are used in logistics. However, the use of terrestrial and aerial logistic assets faces challenges from cargo theft and hijacking. The occurrence of cargo theft and hijacking degrades the resilience of the organizational supply chain. It is important to reduce the success of cargo theft, and organizational loss. The presented research proposes the use of stratosphere based platform for cargo transport to reduce cargo theft and hijacking. The use of stratosphere based platforms is beneficial as its host geographical location, the stratosphere is significantly inaccessible to rogue elements. In addition, stratosphere utilization results in reduced cargo transport time due to the reduced air resistance. The proposed research presents the cargo intelligent network architecture which demonstrates how using stratospheric platforms for cargo transport solutions can address this challenge. Performance evaluation results show that using the proposed mechanism instead of the existing mechanism enhances the number of completed trips and reduces carbon emissions. The number of trips is enhanced by 50.4% on average. The carbon emissions is reduced by 89.6% on average.